Chemical synthesis of human milk oligosaccharides: lacto-N-neohexaose (Galβ1 → 4GlcNAcβ1→)2 3, 6Galβ1 → 4Glc. Issue 9 (12th February 2020) - Bandara, Mithila D.; Stine, Keith J.; Demchenko, Alexei V.
Abstract : The first chemical synthesis of lacto- N -neohexaose (LNnH) has been completed using a convergent synthetic strategy. Abstract : The first chemical synthesis of lacto- N -neohexaose (LNnH) has been completed using a convergent synthetic strategy. The reaction conditions and donor–acceptor combinations have been carefully refined to minimize side reactions and achieve high yields in all glycosylation steps. Lacto- N -neotetraose, another common human milk oligosaccharide, was also synthesized en route to the target LNnH.